The first cat in space and the baby pirate's revenge - Barnett, Mac (Barnett, Mac. First cat in space, 2025)
..."First Cat, LOZ 4000, and the Moon Queen--encounter Captain Babybeard and his crew of swashbuckling pirates. After Captain Babybeard steals a treasure map from the Queen of the Moon, the notorious pirate sees nothing but piles of gold in his future. But a mutiny, led by his first mate, the Martian Pirate James Plantain, leaves Babybeard marooned on a deserted island. Betrayed by his crew, the little captain seeks an unlikely alliance...Will Captain Babybeard get revenge? Will First Cat, the Moon Queen, and LOZ 4000 recover their treasure map? Or will the moon fall into the hands of a nefarious banana?"--Provided by publisher.